Elastic and Inelastic Magnetic Electron Scattering Form Factors of Neutron- Rich 19C Exotic Nucleus - Radhi, R. A.; Dakhil, Z. A.; Hameed, B. S. (Iraqi Journal of Science, 2025)
The elastic magnetic electron scattering form factors and the magnetic dipole moments have been studied for the ground state of 19C (halo) (JπT= 1/2+ 7/2) nucleus carried out using psd-shell Millener-Kurath (PSDMK) interactions. The single-particle wave functions of harmonic-oscillator (HO) potential are used with two different oscillator parameters bcore and bhalo. According to this interaction, the core nucleons of 18C nucleus are assumed to move in the model space of spd. The outer halo (1-neutron) in 19C is assumed to move in the pure 2s1/2 orbit. The elastic magnetic electron scattering of the stable 13C and exotic 19C nuclei are investigated through Plane Wave Born Approximation (PWBA). It is found that the difference between the total form factors of unstable isotope (19C halo and non-halo) and stable isotope 13C is in magnitude. The magnetic dipole moments of excited states 19C (JπT= 3/2+ 7/2) and (JπT= 5/2+ 7/2) nucleus and the transverse inelastic electron scattering form factors for 19C (JπT= 5/2+ 7/2) are also calculated using the Reehal-Widenthal (REWIL) interactions.